2020
DOI: 10.3390/jcm9051557
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Epidemiological Burden of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Across Europe: Current Evidence and EUROMENE Research Recommendations for Epidemiology

Abstract: This review aimed at determining the prevalence and incidence of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) in Europe. We conducted a primary search in Scopus, PubMed and Web of Science for publications between 1994 and 15 June 2019 (PROSPERO: CRD42017078688). Additionally, we performed a backward-(reference lists) and forward-(citations) search of the works included in this review. Grey literature was addressed by contacting all members of the European Network on ME/CFS (EUROMENE). Independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 45 publications
0
43
0
1
Order By: Relevance
“…Future studies should further examine if PEM is a distinct characteristic feature, on which basis a subgroup of CFS patients might be distinguished, or whether PEM is related directionally or non-directionally to other symptoms from which CFS patients suffer. In addition, it was suggested that further multi-center studies on CFS should apply the same protocols [ 46 ]. Therefore, it is necessary to make a decision as to whether PEM should be a symptom required for CFS diagnosis, which would have an impact on the types of criteria of CFS used in research.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should further examine if PEM is a distinct characteristic feature, on which basis a subgroup of CFS patients might be distinguished, or whether PEM is related directionally or non-directionally to other symptoms from which CFS patients suffer. In addition, it was suggested that further multi-center studies on CFS should apply the same protocols [ 46 ]. Therefore, it is necessary to make a decision as to whether PEM should be a symptom required for CFS diagnosis, which would have an impact on the types of criteria of CFS used in research.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ], while Norway and others use diagnostic codes (ICD-10, G.93.3) reported in broader nationwide registries [ 5 ]. As it is unclear if the type of diagnostic criteria or case definitions used influences the findings of primary studies, the way the patients are diagnosed should be clearly stated and, ideally, standardized in future studies [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the illness ranges, from ambulant to housebound [ 5 ]. A 2020 EUROMENE review found that prevalence ranged from 0.1–2.2% [ 6 ]. An American report from 2015, summarizing more than 9000 papers about illness, concluded that “ME/CFS is a serious, chronic, complex, and multisystem disease that frequently and dramatically limits the daily activities of affected patients” [ 7 ].…”
Section: Introductionmentioning
confidence: 99%